Β-NaGdF4:Eu3+ nanocrystal markers for melanoma tumor imaging. Issue 63 (16th June 2016) - Sojka, B.; Podhorodecki, A.; Banski, M.; Misiewicz, J.; Drobczynski, S.; Dumych, T.; Lutsyk, M. M.; Lutsyk, A.; Bilyy, R.
Abstract : Europium doped nanocrystals can be optimized to be successfully used as visualization markers for i.e. melanoma tumor. Abstract : In the current paper, the strategy of tuning the optical and structural properties of Eu doped nanocrystals (NCs) is described with the emphasis on obtaining NCs with high brightness and photostability at the desired excitation and emission range. Those NCs are further chemically functionalized and covalently conjugated with lectins, providing specific (but reversible) targeting of pathological glycans on the surface of melanoma cells. Nanoconjugates are then injected intravenously into the blood stream of laboratory mice. Subsequently, histological slices were examined by fluorescence microscopy, whereas whole melanoma tumor were examined by ex vivo fluorescence imaging. Analysis revealed specific targeting, high intensity and photostability of the signal during visualization.